'You'll see that everywhere': institutional isomorphism in secondary school subject departments - Puttick, Steven (School leadership & management, 2017)
This paper asks why spatially separated school departments might exhibit, in different ways, very similar practices. Data from an ethnographic study of three secondary school geography departments in England are discussed through a concept of 'isomorphism' (homogenising forces), drawn from neo-institutional theory. Similarities across these departments are analysed in terms of coercive isomorphism, including the strong regulatory role played by examination boards and Ofsted; mimetic isomorphism, in which similar approaches are adopted in response to situations of high uncertainty, based on spreading good practice; and normative isomorphism, including the implications of closely guarded educational routes, the professionalisation of teaching, and wider social trends including the increasing use of Google as a source of knowledge for lessons. It is argued that evidence of homogeneity across spatially separated departments raises interesting questions about teachers' practice, with implications for departmental and school leadership.